The identity and methylation status of the first transcribed nucleotide in eukaryotic mRNA 5′ cap modulates protein expression in living cells. Issue 4 (27th January 2020) - Sikorski, Pawel J; Warminski, Marcin; Kubacka, Dorota; Ratajczak, Tomasz; Nowis, Dominika; Kowalska, Joanna; Jemielity, Jacek
Abstract: 7-Methylguanosine 5′ cap on mRNA is necessary for efficient protein expression in vitro and in vivo . Recent studies revealed structural diversity of endogenous mRNA caps, which carry different 5′-terminal nucleotides and additional methylations (2′- O -methylation and m 6 A). Currently available 5′-capping methods do not address this diversity. We report trinucleotide 5′ cap analogs (m 7 GpppN(m) pG), which are utilized by RNA polymerase T7 to initiate transcription from templates carrying Φ6.5 promoter and enable production of mRNAs differing in the identity of the first transcribed nucleotide (N = A, m 6 A, G, C, U) and its methylation status (±2′- O -methylation). HPLC-purified mRNAs carrying these 5′ caps were used to study protein expression in three mammalian cell lines (3T3-L1, HeLa and JAWS II). The highest expression was observed for mRNAs carrying 5′-terminal A/Am and m 6 Am, whereas the lowest was observed for G and Gm . The mRNAs carrying 2′- O -methyl at the first transcribed nucleotide (cap 1) had significantly higher expression than unmethylated counterparts (cap 0) only in JAWS II dendritic cells. Further experiments indicated that the mRNA expression characteristic does not correlate with affinity for translation initiation factor 4E or in vitro susceptibility to decapping, but instead depends on mRNA purity and the immune state of the cells.